KARAKTER HUMANIS DALAM NOVEL BUMI MANUSIA DAN EMILIE JAWA 1904 - Adek Dwi Oktaviantina (Multilingual, 2015)
The struggle for independence movement grew among youth begins with anawareness of humanism nationality. Novel Bumi Manusia by Pramoedya Ananta Toerand Emilie Jawa 1904 novel is a historical romance that revolves around the youthmovement in the early days of the freedom movement and reveals the humanistconsciousness through both thought the main character of the novel. The movement ofindependence struggle that grew among youths begins with an awareness ofhumanism nationality. Bumi Manusia Novel which is created by Pramoedya AnantaToer and Emilie Jawa 1904 are historical romances that tells about the youthmovement in the early days of the freedom movement and reveals the humanistconsciousness through the thought of both main character of the novel. The methodsof this research is descriptive qualitative method. The purpose is to describe thesimiliarity of Minke and Emilie's thought of humanism in the colony. The result showsthere is a similarity of thought between both characters, which is about theadmiration toward the inspiring of the struggle character also toward the activistsassociation. The differences are Minke distribute his aspirations through writing innewspapers meanwhile Emilie distribute her aspirations with supporting thehumanism movement that is done by the indigene people. Other differences are theviewpoints of Minke as a young man from a colonized country and the viewpoints ofEmilie as a woman from Europe, a colonial country.